2005
DOI: 10.1177/1049731505275060
|View full text |Cite
|
Sign up to set email alerts
|

A Fidelity Rating Instrument for Consumer-Run Drop-in Centers (FRI-CRDI)

Abstract: Objective: Given the present emphasis on accountability and maintaining quality, the objective of this study was to develop, apply, and assess the reliability of a fidelity rating instrument for consumer-operated services-a promising model, but one for which fidelity criteria are not yet established. Method: Based on observations, documents, and director interviews from 31 consumer-run drop-in centers, we developed a scale measuring fidelity to pre-established criteria and rated each center on scale items. A s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…Data were originally collected to develop fidelity criteria and measures for CRDIs; for comparative purposes, parallel data were collected from clubhouses serving the same geographic areas (see Mowbray et al. 14 for additional information). Data collection took place at 31 CRDI centers and 31 clubhouses located in diverse geographical areas of the state of Michigan.…”
Section: Introductionmentioning
confidence: 99%
“…Data were originally collected to develop fidelity criteria and measures for CRDIs; for comparative purposes, parallel data were collected from clubhouses serving the same geographic areas (see Mowbray et al. 14 for additional information). Data collection took place at 31 CRDI centers and 31 clubhouses located in diverse geographical areas of the state of Michigan.…”
Section: Introductionmentioning
confidence: 99%
“…Such programs have been defined as service organizations in which the paid staff and most of the governing board are themselves users of mental health services (1). Studies have shown that consumer-run mental health services promote personal and organizational empowerment (2), increase hope (3), enhance independence and competence (4), counteract typical feelings of powerlessness (5), cocreate narratives that support recovery (6,7), and promote social support (4,8,9).…”
mentioning
confidence: 99%
“…However, measurements of peer organizations' fulfilment of such "critical ingredients" have revealed a substantial lack of consistency. Mowbray et al (2005; p. 279) argue that peer organizations' heterogeneity is reflective of "the barriers they often face in start-up, such as lack of funding and support from traditional mental health providers". Such challenges increase the risk of "programme drift" whereby peer organizations independence and fidelity to intended values and principles are compromised or altered (Beales & Wilson, 2015;Mowbray et al, 2005).…”
Section: Peer Supp Ort In Peer Org Aniz Ationsmentioning
confidence: 99%
“…In practical terms, this means that a participatory, nonhierarchical and shared leadership structure is evident, which SAMHSA (; p.10) argues enables a “permeability of power within the organization among management, staff, and members”. Peers therefore perform different roles within the organization, including serving as paid or volunteer staff and as board members and officers (Johnsen, Teague, & McDonel‐Herr, ; Mowbray, Holter, Stark, Pfeffer, & Bybee, ). Furthermore, the programmes and initiatives delivered in these organizations are led by the members and driven by members’ needs and preferences.…”
Section: Peer Support In Peer Organizationsmentioning
confidence: 99%